STABILITAS HASIL LIMA KULTIVAR GANDUM - Inayah, Suwaibah Ummul; Purwantoro, Aziz; Supriyanta, Supriyanta (Jurnal Ilmu-Ilmu Pertanian, 2005)
Indonesia has been trying to devolop tropical wheat in regard to decrease import of wheat. Therofore, some tropical wheat varieties have been introduced into Indonesia. This research aims to evaluate the yield stability of some varieties which introduced into Indonesia. Five varieties of wheat , nantely Dll/R 162, DlyR 195, HD 2189, HUII/ 234, and Nias as check variety, were grown at three different environments. Field experiment were arranged according to Randonrizecl Completely Block Design procedure with three replications. The result showed that based on the stability parameter of Eberhart and Russel, HUII/ 234 is stable cultivar in yield and yield components, although its yield is Erite anall. The other two arltivars, nantely Dll/ll 195 and Nias tend to adapt in favorable environment. Meanwhile, HD 2lB9 and DIYR 162 are suitable varieties for less favorable environment,